Family Treatment Strategies to Reduce Distress Among Family Members of Palliative Patients in the ICU - Rhomadona Putra; Nurul Huda; Erika (Fakultas Keperawatan Universitas Andalas, 2026)
Psychological problems are often faced by families when a member is hospitalized in the Intensive Care Unit (ICU). One of the most psychological problems often found in family members is psychological distress. An intervention applied to relief this problem is family treatment. This study aimed to identify family treatment strategies to reduce distress among family members of palliative patients in ICU.An experimental research approach with one group pre-test post-test 15 family members of intensive care unit (ICU) patients were selected. Samples were collected using purposive sampling based on inclusion criteria. The respondent received family treatment which focus on family involvement, education and communication in addition to standard treatment. Distress Thermometer were used to measure study parameters. Data was analyzed using Wilcoxon test. The statistic test showed that majority of respondents were women (93.3%) in the early adult age (26-35 years old) (33.3%), working (53.3%) then having a relationship with patients as nuclear family (73.3%). Most respondents reported sleep problems (60%), anxiety (80%), depression (53.3%), grief and loss (53.3%), and fear (53.3%). Family’s treatment strategies were highly effective (p<0.001) in reducing distress in family member of palliative patients. The family’s treatment strategies were proven to be effective in reducing distress among family of palliative’s patients in ICU. Study recommends the use of family’s treatment strategies packages a means of strategies to reduce family’s distress during their companion in ICU.